Catalyst for preparing acrylonitrile through propylene ammoxidation as well as preparation method and application of catalyst

By controlling the proportion of LA, R and Q in catalysts, a stable molybdenum acid rare earth phase is formed, which solves the problem of low existing catalyst activity and high two carbon revenue. Essence

CN119368195AActive Publication Date: 2025-01-28CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310918396.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

The existing acrylonitrile catalysts are low in activity and high in yields of two carbons.

Method used

By controlling the proportion of LA elements and other rare earth element R, and the ratio of Q to rare earth elements, the molybdenum acid rare earth phase and activity are formed to form a solid solution. And improve catalyst stability.

Benefits of technology

The high activity and low carbon revenue of the catalysts are realized, the stability and activity of the catalyst is improved, and the high selectivity and stability of the acrylic oxidation reaction is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004357802570000102
    Figure BDA0004357802570000102
  • Figure BDA0004357802570000111
    Figure BDA0004357802570000111
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing acrylonitrile through propylene ammoxidation as well as a preparation method and application of the catalyst. Active components of the catalyst comprise La, Q and R, R is at least one of Ce, Pr, Nd, Sm and Eu, and Q is at least one of Zr, Ca, Ti and P; the atomic ratio of La to R is 0.05 to 0.45, and the atomic ratio of Q / (La + R) is 0.01 to 0.25. When the catalyst is used for preparing acrylonitrile through propylene ammoxidation, the catalyst has the characteristics of high activity and low two-carbon yield in a long-period operation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ammoxidation catalyst, in particular to a catalyst for preparing acrylonitrile by ammoxidation of propylene, and a preparation method and application thereof. Background Art

[0002] Acrylonitrile is mainly used to produce acrylic fiber, ABS plastic, styrene plastic, acrylamide, etc. It is an important chemical raw material. In industry, propylene is mainly used as raw material to produce acrylonitrile by fluidized bed ammoxidation. Although the technology of propylene ammoxidation to acrylonitrile has been successfully industrialized in acrylonitrile plants around the world, the catalyst for propylene ammoxidation to acrylonitrile, one of the core technologies of the process, is still under continuous research and development in order to prepare catalysts with better comprehensive properties such as activity, selectivity, and stability.

[0003] At present, Mo-Bi catalysts have been widely used in industry. CN1600423A discloses a method for preparing a fluidized bed catalyst for olefin ammoxidation reaction, wherein the catalyst uses silicon dioxide as a carrier, the carrier accounts for 30-50wt% of the total catalyst, and the active component is composed of the general formula Mo (12-g) Bi a Fe b Ni c X d Y e Z f Q g O x Indicated, wherein X is Mg, Co, Ca, etc.; Y is La, Ce, Sm, etc.; Z is Li, K, Rb, etc.; Q is B, W, P, etc.; a-f are the atomic numbers of the corresponding elements. The catalyst preparation method comprises dissolving the starting material of the metal element to prepare a mixed salt solution, and co-precipitating it with the starting material of the carrier to prepare a slurry, spray drying the slurry after aging, and calcining the dried particles at high temperature to obtain the finished catalyst.

[0004] For the catalyst of propylene ammoxidation to acrylonitrile, developing Mo-Bi catalysts with both high activity and low two-carbon yield has been a goal that has been studied hard in this field. Summary of the invention

[0005] In order to solve the problems of low catalyst activity and high two-carbon yield in the prior art of preparing acrylonitrile by propylene ammoxidation, the present invention provides a catalyst for preparing acrylonitrile by propylene ammoxidation and a preparation method and application thereof. The catalyst for preparing acrylonitrile by propylene ammoxidation has high activity and low two-carbon yield.

[0006] A first aspect of the present invention provides a catalyst for preparing acrylonitrile by ammoxidation of propylene, wherein the active components of the catalyst include La, Q and R, wherein R is at least one of Ce, Pr, Nd, Sm, and Eu, and Q is at least one of Zr, Ca, Ti, and P elements; the atomic ratio of La / R is 0.05-0.45, and the atomic ratio of Q / (La+R) is 0.01-0.25.

[0007] Furthermore, the atomic ratio of La / R is 0.08-0.40, and the atomic ratio of Q / (La+R) is 0.01-0.20.

[0008] Furthermore, the active component is a composite oxide, and the active component includes Mo, Bi, Fe, alkali metal elements, alkaline earth metal elements and other elements A in addition to La, Q and R.

[0009] Furthermore, the catalyst also includes a carrier, and the carrier is preferably silicon dioxide.

[0010] Furthermore, based on the weight of the catalyst, the content of the active component in terms of oxide is 30%-90%, and the content of the carrier is 10%-70%.

[0011] Furthermore, the alkali metal element is selected from at least one of Li, Na, K, Rb and Cs; the alkaline earth metal element is selected from at least one of Be, Mg, Sr and Ba; and the other element A is selected from at least one of W, V, Nb, Ni, Co, Cr, Mn, Tl, Au, Ag, Pt, Ru, Rh, Pd, Sb, In, Sn, Te and In.

[0012] Furthermore, among the active components, based on the weight of the catalyst,

[0013] The weight content of the Mo element calculated as MoO3 is 15%-55%, preferably 20%-45%,

[0014] The weight content of the Bi element calculated as Bi2O3 is 0.5%-3.5%, preferably 1.0%-3.5%,

[0015] The weight content of the Fe element calculated as Fe2O3 is 1%-12%, preferably 1.5%-11%.

[0016] The weight content of the La element and the R element calculated as corresponding oxides is 1.5%-8.5%, preferably 2.5%-5.0%.

[0017] The weight content of the Q element in terms of oxide is 0.01%-5.0%, preferably 0.01%-3.5%.

[0018] The weight content of the alkali metal element calculated as oxide is 0.01%-0.60%, preferably 0.05%-0.55%,

[0019] The weight content of the alkaline earth metal in terms of oxide is 0.01%-4.0%, preferably 0.5%-2.5%.

[0020] The weight content of the other element A calculated as oxide is 0.01%-15%, preferably 0.05%-14%.

[0021] Furthermore, in the active component, the atomic ratio of Bi / Mo is 0.008-0.25, preferably 0.01-0.20; examples include but are not limited to: 0.02, 0.04, 0.05, 0.06, 0.07, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20 and the like.

[0022] Furthermore, in the active component, the atomic ratio of Fe / Bi is 1.0-12.0, preferably 1.5-11.0; examples include but are not limited to: 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0 and the like.

[0023] Furthermore, in the active component, the atomic ratio of (La+R+alkali metal element+alkaline earth metal element) / Mo is 0.05-0.4, preferably 0.10-0.35; examples include but are not limited to: 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35 and the like.

[0024] Furthermore, in the active component, the atomic ratio of A / Mo is 0.01-1.0, preferably 0.02-0.90; examples include but are not limited to: 0.02, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 045, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90 and the like.

[0025] The second aspect of the present invention provides a method for preparing the catalyst for preparing acrylonitrile by propylene ammoxidation, comprising the following steps:

[0026] (1) Precursors of La, R, Q and part of Mo are mixed and heat treated to form a mixed solution I;

[0027] (2) mixing precursors of active components except La, R, Q, and Mo to form a solution I;

[0028] (3) mixing the remaining Mo precursor and the carrier precursor to form a mixed solution II, adding the mixed solution I and the solution I, and performing a heat treatment to form a slurry I;

[0029] (4) spray drying the slurry I to obtain granules;

[0030] (5) calcining the particles to obtain the catalyst.

[0031] Furthermore, the heating rate of the heat treatment in step (1) is controlled at 5-20°C / min, the heat treatment temperature is controlled at 50-120°C, and the constant temperature is maintained for 5-20min.

[0032] Furthermore, the heating rate of the heat treatment in step (3) is controlled at 8-20°C / min, the heat treatment temperature is controlled at 100-150°C, and the constant temperature is maintained for 5-20min.

[0033] Furthermore, the carrier precursor described in step (3) is a silicon dioxide precursor, preferably a silica sol, wherein the solid content of the silica sol is 20 wt%-50 wt% in terms of silicon dioxide, and the average particle size distribution is 10-35 nm.

[0034] Furthermore, there is no particular limitation on the ratio or amount of the La element precursor, R element precursor, Q element precursor, Mo element precursor and other element precursors (Fe element precursor, alkali metal element precursor, alkaline earth metal element precursor, other element A precursor) and carrier precursor, as long as the content of each component in the final catalyst particles meets the requirements.

[0035] Furthermore, the Mo element introduced into the catalyst in step (1) accounts for 40%-80% of the total MoO3 content in the catalyst, calculated as MoO3, and preferably 40%-70%.

[0036] Furthermore, there is no particular limitation on the Mo element precursor, which may be an oxide of Mo or any substance that can generate the oxide after calcination, and specifically includes oxides, hydroxides, inorganic acid salts, organic acid salts and ammonium salts of oxygen-containing acids (including hydrates of these compounds) of Mo, among which water-soluble inorganic acid salts, water-soluble organic acid salts and ammonium salts of oxygen-containing acids of Mo are preferred, and ammonium salts of oxygen-containing acids of Mo are more preferred, such as (NH4)6Mo7O 24 or a hydrate thereof.

[0037] Further, there is no particular limitation on the precursors of Bi element, Fe element, La element, R element, Q element, alkali metal element, alkaline earth metal element and other element A, and they can be oxides of the corresponding elements or any substance that can generate the oxides after calcination, such as oxides, hydroxides, inorganic acid salts and organic acid salts (including hydrates of these compounds) of the corresponding elements, preferably water-soluble inorganic acid salts and water-soluble organic acid salts, more preferably halides, alcohol salts, nitrates and acetates, especially nitrates. These precursors can be used alone or in combination in any proportion.

[0038] Furthermore, the spray drying conditions in step (4) include: the drying heat source is air, the drying temperature is 250-350°C, preferably 300-350°C, the drying time is 0.1-2.0h, preferably 0.2-1.0h, and the average diameter of the spray droplets is 20-200μm, preferably 40-180μm.

[0039] Furthermore, the calcination in step (5) is carried out in two stages, the first stage calcination conditions are: calcination temperature of 200-300°C, calcination time of 0.5-5h, and heating rate of 1-5°C / min; the second stage calcination conditions are: calcination temperature of 500-750°C, calcination time of 0.5-5h, and heating rate of 8-20°C / min. The calcination is carried out in an oxygen-containing atmosphere. In the oxygen-containing atmosphere, the volume content of oxygen is generally greater than 0% and less than 100%, preferably greater than 0% and less than 50%, relative to the total volume of the oxygen-containing atmosphere.

[0040] The third aspect of the present invention provides a method for preparing acrylonitrile by ammoxidation of propylene, comprising: in the presence of the above catalyst or the catalyst prepared by the above preparation method, ammoxidation of propylene to produce acrylonitrile, the reaction conditions are: the molar ratio of propylene: ammonia: air is 1: 1.1-1.35: 9.5-10, the reaction temperature is 420-440°C, the reaction pressure is 0.03-0.14MPa in gauge pressure, and the weight hourly space velocity is 0.04-0.10h- 1 .

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. The inventors have found through research that by controlling the ratio of La element to other rare earth elements R (Ce, Pr, Nd, Sm, Eu), and the ratio of Q to rare earth elements (La+R) in the catalyst for preparing acrylonitrile by propylene ammoxidation, the rare earth molybdate phase formed can form a solid solution with the active phase, thereby stabilizing the existence of the active phase and not generating other phases, thereby ensuring that the catalyst has high activity and low two-carbon yield.

[0043] 2. The present invention controls the method of first mixing the raw materials of Q, rare earth (La and R) and part of Mo in the catalyst preparation process, so as to facilitate the rare earth molybdate and Q to form a more stable phase; at the same time, the heat treatment and calcination process in the catalyst preparation process can significantly reduce the two carbon yields and improve the catalyst stability. The possible reason is that the stable ratio of the crystal phase on the catalyst surface is conducive to the sufficient active sites of the catalyst during the reaction process to adsorb and react the reaction gas, so that the reaction is carried out stably and moderately with high selectivity, and the problem of excessively high two carbon yields is effectively controlled.

[0044] 3. When the catalyst of the present invention is used for preparing acrylonitrile by propylene ammoxidation, it has a lower two-carbon yield and can significantly improve the stability and activity of the catalyst. DETAILED DESCRIPTION

[0045] In the present invention, the two carbons refer to CO and CO2, and the yield of the two carbons (%) = (total moles of carbon monoxide and carbon dioxide generated by the reaction / moles of propylene feed in terms of carbon moles) × 100%.

[0046] In the present invention, the definitions of propylene conversion and acrylonitrile selectivity are as follows:

[0047] Propylene conversion rate (%) = (moles of propylene consumed in the reaction / moles of propylene fed) × 100%,

[0048] Acrylonitrile selectivity (%) = (the number of moles of acrylonitrile produced by the reaction / the number of moles of acrylonitrile consumed by the reaction) × 100%.

[0049] The present invention will be further described below by way of examples.

[0050] Example 1

[0051] 521 g (NH4)6Mo7O 24 ·4H2O was dissolved in water, 2.21 g ZrO2, 77.2 g Pr(NO3)3·6H2O and 25.6 g La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 80°C at a rate of 10°C / min and kept constant for 15 min; 3.64 g KOH, 798.9 g Fe(NO3)3·9H2O, 173.9 g Bi(NO3)3·5H2O, 526.6 g Ni(NO3)2·6H2O and 137.9 g Mg(NO3)2·6H2O were added to water and dissolved to obtain solution I; 306.0 g (NH4)6Mo7O 244H2O was dissolved in water, 2750 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 150°C at a rate of 10°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to 300°C, and the temperature was kept for 30 min, and then the temperature was raised to 550°C at 20°C / min and the temperature was kept for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0052] 50% Zr 0.05 K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 0.5 La 0.18 Bi 1.0 Mo 13 O x +50%SiO2

[0053] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0054] Example 2

[0055] 526.5 g (NH4)6Mo7O 24 ·4H2O was dissolved in water, 3.57 g of Ca(NO3)2·6H2O, 78.7 g of Nd(NO3)3·6H2O and 21.6 g of La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 100°C at a heating rate of 5°C / min and kept constant for 10 min; 3.68 g of KOH, 807.4 g of Fe(NO3)3·9H2O, 87.9 g of Bi(NO3)3·5H2O, 527.2 g of Co(NO3)2·6H2O, 128.4 g of Mn(NO3)2, 139.3 g of Mg(NO3)2·6H2O and 6.12 g of AgNO3 were added to water and dissolved to obtain solution I; 309.2 g of (NH4)6Mo7O 244H2O was dissolved in water, 2750 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 120°C at a rate of 10°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to rise to 300°C, and stayed for 30 min, and then raised to 550°C at 20°C / min, and stayed for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0056] 50% Ca 0.08 Ag 0.1 K 0.15 Fe 5.46 Co 5.0 Mn 1.0 Mg 1.5 Nd 0.5 La 0.15 Bi 0.5 Mo 13 O x +50%SiO2

[0057] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0058] Example 3

[0059] 755.8 g (NH4)6Mo7O 24 ·4H2O was dissolved in water, 6.41 g ZrO2, 67.8 g Ce(NO3)3·6H2O and 24.8 g La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 120°C at a heating rate of 10°C / min and kept constant for 8 min; 11.5 g RbNO3, 1159 g Fe(NO3)3·9H2O, 126.1 g Bi(NO3)3·5H2O, 756.8 g Co(NO3)2·6H2O, 184.2 g Mg(NO3)2·6H2O, 5.25 g Cr2O3 and 4.4 g AgNO3 were added to water and dissolved to obtain solution I; 443.9 g (NH4)6Mo7O24 4H2O was dissolved in water, 1650 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 100°C at a rate of 10°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to 300°C, and the temperature was kept for 30 min, and then the temperature was raised to 550°C at 20°C / min and the temperature was kept for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0060] 70% Zr 0.10 Ag 0.05 R 0.15 Fe 5.46 Co 5.0 Cr 0.1 Mg 1.5 La 0.12 Ce 0.3 Bi 0.5 Mo 13 O x +30%SiO2

[0061] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h- 1 ; Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0062] Example 4

[0063] 646.8 g (NH4)6Mo7O 24·4H2O was dissolved in water, 1.65 g ZrO2, 38.8 g Sm(NO3)3·6H2O and 8.8 g La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 80°C at a rate of 20°C / min and kept constant for 15 min; 9.85 g RbNO3, 991.8 g Fe(NO3)3·9H2O, 108 g Bi(NO3)3·5H2O, 653.8 g Ni(NO3)2·6H2O, 171.2 g Mg(NO3)2·6H2O, 4.5 g Cr2O3 and 11.28 g AgNO3 were added to water and dissolved to obtain solution I; 379.9 g (NH4)6Mo7O 24 4H2O was dissolved in water, 2200 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 150°C at a rate of 20°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to rise to 300°C, and stayed for 20 min, and then raised to 550°C at 20°C / min, and stayed for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0064] 60% Zr 0.03 Ag 0.15 R 0.15 Fe 5.46 Ni 5.0 Cr 0.1 Mg 1.5 Sm 0.5 La 0。05 Bi 0.5 Mo 13 O x +40%SiO2

[0065] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0066] Example 5

[0067] 646.0 g (NH4)6Mo7O 24·4H2O was dissolved in water, 2.74 g ZrO2, 38.8 g Sm(NO3)3·6H2O and 21.2 g La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 80°C at a heating rate of 10°C / min and kept at this temperature for 15 min; 9.83 g RbNO3, 990.7 g Fe(NO3)3·9H2O, 107.8 g Bi(NO3)3·5H2O, 653 g Ni(NO3)2·6H2O, 171 g Mg(NO3)2·6H2O, 4.49 g Cr2O3 and 6.65 g In(NO3)3 were added to water and dissolved to obtain solution I; 379.4 g (NH4)6Mo7O 24 4H2O was dissolved in water, 2200 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 120°C at a rate of 20°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to rise to 300°C, and stayed for 10 min, and then raised to 550°C at 20°C / min and stayed for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0068] 60% Zr 0.05 In 0.05 R 0.15 Fe 5.46 Ni 5.0 Cr 0.1 Mg 1.5 Sm 0.5 La 0。12 Bi 0.5 Mo 13 O x +40%SiO2

[0069] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0070] Example 6

[0071] 642.9 g (NH4)6Mo7O24 ·4H2O was dissolved in water, 2.73 g ZrO2, 95.3 g Pr(NO3)3·6H2O and 14.1 g La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 80°C at a heating rate of 10°C / min and kept constant for 15 min; 6.52 g RbNO3, 985.9 g Fe(NO3)3·9H2O, 107.3 g Bi(NO3)3·5H2O, 649.9 g Ni(NO3)2·6H2O, 156.7 g Mg(NO3)2·6H2O, 4.47 g CrO3 and 13.24 g In(NO3)3 were added to water and dissolved to obtain solution I; 377.6 g (NH4)6Mo7O 24 4H2O was dissolved in water, 2200 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 100°C at a rate of 20°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to rise to 300°C, and stayed for 20 min, and then raised to 550°C at 20°C / min, and stayed for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0072] 60% Zr 0.05 In 0.1 R 0.10 Fe 5.46 Ni 5.0 Cr 0.1 Mg 1.5 Pr 0.5 La 0.08 Bi 0.5 Mo 13 O x +40%SiO2

[0073] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h- 1 ; Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0074] Comparative Example 1

[0075] 2.21 g of ZrO2, 77.2 g of Pr(NO3)3·6H2O, 25.6 g of La(NO3)3·6H2O, 3.64 g of KOH, 798.9 g of Fe(NO3)3·9H2O, 173.9 g of Bi(NO3)3·5H2O, 526.6 g of Ni(NO3)2·6H2O and 137.9 g of Mg(NO3)2·6H2O were dissolved in water to obtain solution I. 827.0 g of (NH4)6Mo7O 24 4H2O was dissolved in water, 2750 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution I, and then solution I was added and stirred, and then the temperature was raised to 150°C at a rate of 10°C / min and kept constant for 15 min to form slurry I; the prepared slurry I was subjected to micro-spheroidal molding in a spray dryer, the drying temperature was 300°C, the drying time was 0.5 h, and the average diameter of the spray droplets was 100 μm to obtain particles; finally, it was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to 300°C, and the temperature was kept for 30 min, and then the temperature was raised to 550°C at 20°C / min and the temperature was kept for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0076] 50% Zr 0.05 K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 0.5 La 0.18 Bi 1.0 Mo 13 O x +50%SiO2

[0077] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h- 1 ; Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0078] Comparative Example 2

[0079] 521 g (NH4)6Mo7O 24·4H2O was dissolved in water, 2.22 g ZrO2 and 77.8 g Pr(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 80°C at a heating rate of 10°C / min and kept at a constant temperature for 15 min; 3.67 g KOH, 804.6 g Fe(NO3)3·9H2O, 175.1 g Bi(NO3)3·5H2O, 530.4 g Ni(NO3)2·6H2O and 138.9 g Mg(NO3)2·6H2O were added to water and dissolved to obtain solution I; 306.0 g (NH4)6Mo7O 24 4H2O was dissolved in water, 2750 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 150°C at a rate of 10°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to 300°C, and the temperature was kept for 30 min, and then the temperature was raised to 550°C at 20°C / min and the temperature was kept for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0080] 50% Zr0 .05 K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 0.5 Bi 1.0 Mo 13 O x +50%SiO2

[0081] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h- 1 ; Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0082] Comparative Example 3

[0083] 521 g (NH4)6Mo7O 24·4H2O was dissolved in water, 77.2 g of Pr(NO3)3·6H2O and 25.6 g of La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 80°C at a heating rate of 10°C / min and kept at a constant temperature for 15 min; 3.64 g of KOH, 798.9 g of Fe(NO3)3·9H2O, 173.9 g of Bi(NO3)3·5H2O, 526.6 g of Ni(NO3)2·6H2O and 137.9 g of Mg(NO3)2·6H2O were added to water and dissolved to obtain solution I; 306.0 g of (NH4)6Mo7O 24 4H2O was dissolved in water, 2750 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 150°C at a rate of 10°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-spheroidal molding in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the slurry was calcined in an air atmosphere, and the calcination temperature was controlled at 5°C / min to 300°C, and the temperature was kept for 30 min, and then the temperature was raised to 550°C at 20°C / min and the temperature was kept for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0084] 50%K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 0.5 La 0.18 Bi 1.0 Mo 13 O x +50%SiO2

[0085] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h- 1 ; Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0086] Comparative Example 4

[0087] 521 g (NH4)6Mo7O 24·4H2O was dissolved in water, 2.21 g ZrO2, 77.2 g Pr(NO3)3·6H2O and 25.6 g La(NO3)3·6H2O were added to form a mixed solution I, and the temperature was raised to 80°C at a rate of 10°C / min and kept constant for 15 min; 3.64 g KOH, 798.9 g Fe(NO3)3·9H2O, 173.9 g Bi(NO3)3·5H2O, 526.6 g Ni(NO3)2·6H2O and 137.9 g Mg(NO3)2·6H2O were added to water and dissolved to obtain solution I; 306.0 g (NH4)6Mo7O 24 4H2O was dissolved in water, 2750 g of silica sol with a weight concentration of 40% was added, and stirred for 30 min to form a mixed solution II. After adding the mixed solution I and stirring, solution I was added and stirred, and then the temperature was raised to 150°C at a rate of 10°C / min and kept constant for 15 min to form a slurry I. The prepared slurry I was subjected to micro-sphere forming in a spray dryer at a drying temperature of 300°C, a drying time of 0.5 h, and an average diameter of the spray droplets of 100 μm to obtain particles. Finally, the mixture was calcined in an air atmosphere, raised to 550°C, and kept for 45 min. The composition of the catalyst obtained according to the above steps is expressed as follows:

[0088] 50% Zr 0.05 K 0.15 Fe 5.46 Ni 5.0 Mg 1.5 Pr 0.5 La 0.18 Bi 1.0 Mo 13 O x +50%SiO2

[0089] The reaction conditions for producing acrylonitrile by propylene ammoxidation of the above catalyst are: In the millimeter fluidized bed reactor, the catalyst particle size is 50 microns, the reaction temperature is 430°C; the reaction pressure is 0.084MPa; the catalyst loading is 300g; the catalyst propylene load (WWH): 0.085h -1 ; Raw material ratio (molar): C3 = / NH3 / air=1 / 1.25 / 9.6. After running for 1000 hours. The reaction results are shown in Table 1.

[0090] Table 1

[0091]

[0092]

[0093] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A catalyst for preparing acrylonitrile by ammoxidation of propylene, characterized in that: The active components of the catalyst include La, Q and R, R is at least one of Ce, Pr, Nd, Sm, and Eu elements, and Q is at least one of Zr, Ca, Ti, and P elements; the atomic ratio of La to R is 0.05-0.45, and the atomic ratio of Q / (La+R) is 0.01-0.

25.

2. The catalyst according to claim 1, characterized in that The atomic ratio of La to R is 0.08-0.40, and the atomic ratio of Q / (La+R) is 0.01-0.

20.

3. The catalyst according to claim 1, characterized in that The active components of the catalyst also include Mo, Bi, Fe, alkali metal elements, alkaline earth metal elements and other elements A; the other elements A are selected from at least one of W, V, Nb, Ni, Co, Cr, Mn, Tl, Au, Ag, Pt, Ru, Rh, Pd, Sb, In, Sn and Te; and / or, the catalyst also includes a carrier, and the carrier is preferably silicon dioxide.

4. The catalyst according to claim 1, characterized in that The alkali metal element is selected from at least one of Li, Na, K, Rb and Cs; and / or the alkaline earth metal element is selected from at least one of Be, Mg, Sr and Ba.

5. The catalyst according to any one of claims 1 to 4, characterized in that Based on the weight of the catalyst, the content of the active component in terms of oxide is 30%-90%, and the content of the carrier is 10%-70%.

6. The catalyst according to claim 3 or 4, characterized in that The active components are based on the weight of the catalyst. The weight content of the Mo element calculated as MoO3 is 15%-55%, preferably 20%-45%, The weight content of the Bi element calculated as Bi2O3 is 0.5%-3.5%, preferably 1.0%-3.5%, The weight content of the Fe element calculated as Fe2O3 is 1%-12%, preferably 1.5%-11%. The weight content of the La element and the R element calculated as corresponding oxides is 1.5%-8.5%, preferably 2.5%-5.0%. The weight content of the Q element in terms of oxide is 0.01%-5.0%, preferably 0.01%-3.5%. The weight content of the alkali metal element calculated as oxide is 0.01%-0.60%, preferably 0.05%-0.55%, The weight content of the alkaline earth metal in terms of oxide is 0.01%-4.0%, preferably 0.5%-2.5%. The weight content of the other element A calculated as oxide is 0.01%-15%, preferably 0.05%-14%.

7. The catalyst according to any one of claims 3, 4 or 6, characterized in that In the active components, the atomic ratio of Bi / Mo is 0.008-0.25, preferably 0.01-0.20; the atomic ratio of Fe / Bi is 1.0-12.0, preferably 1.5-11.0; the atomic ratio of (La+R+alkali metal elements+alkaline earth metal elements) / Mo is 0.05-0.4, preferably 0.10-0.35; the atomic ratio of A / Mo is 0.01-1.0, preferably 0.02-0.

90.

8. A method for preparing a catalyst according to any one of claims 1 to 7, comprising the following steps: (1) Precursors of La, R, Q and part of Mo are mixed and heat treated to form a mixed solution I; (2) mixing precursors of active components other than La, R, Q, and Mo to form a solution I; (3) mixing the remaining Mo and the carrier precursor to form a mixed solution II, adding the mixed solution I and the solution I, and performing a heat treatment to form a slurry I; (4) spray drying the slurry I to obtain granules; (5) calcining the particles to obtain the catalyst particles.

9. The preparation method according to claim 8, characterized in that: The heating rate of the heat treatment in step (1) is controlled at 5-20°C / min, the heat treatment temperature is controlled at 50-120°C, and the constant temperature is maintained for 5-20min; And / or, the heating rate of the heat treatment in step (3) is controlled at 8-20°C / min, the heat treatment temperature is controlled at 100-150°C, and the constant temperature is maintained for 5-20 min.

10. The preparation method according to claim 8, characterized in that: The carrier precursor described in step (3) is a silicon dioxide precursor, preferably a silica sol, wherein the solid content of the silica sol is 20wt%-50wt% in terms of silicon dioxide, and the average particle size distribution is 10-35nm.

11. The preparation method according to claim 8, characterized in that: The spray drying conditions in step (4) include: the drying heat source is air, the drying temperature is 250-350°C, preferably 300-350°C, the drying time is 0.1-2.0h, preferably 0.2-1.0h, and the average diameter of the spray droplets is 20-200μm, preferably 40-180μm; and / or, the roasting in step (5) is carried out in two stages, the first stage roasting conditions are: roasting temperature is 200-300°C, roasting time is 0.5-5h, and heating rate is 1-5°C / min; the second stage roasting conditions are: roasting temperature is 500-750°C, roasting time is 0.5-5h, and heating rate is 8-20°C / min; the roasting is carried out in an oxygen-containing atmosphere.

12. A method for preparing acrylonitrile by ammoxidation of propylene, comprising: In the presence of the catalyst for preparing acrylonitrile by ammoxidation of propylene as claimed in any one of claims 1 to 7 or the catalyst particles for preparing acrylonitrile by ammoxidation of propylene prepared by the preparation method as claimed in any one of claims 8 to 11, propylene undergoes ammoxidation reaction to produce acrylonitrile.

13. The method according to claim 12, characterized in that The reaction conditions for the ammoxidation of propylene to produce acrylonitrile include: a molar ratio of propylene / ammonia / air of 1:1.1-1.35:9.5-10, a reaction temperature of 420-440°C, a reaction pressure of 0.03-0.14 MPa in gauge pressure, and a weight hourly space velocity of 0.04-0.10 h -1 .

Citation Information

Patent Citations

  • Method for preparing fluid bed catalyst in use for ammoxidation reaction of olefin

    CN1600423A

  • Composite oxide catalyst and preparation method thereof

    CN110227482A

  • Catalyst for preparing acrylonitrile through propylene ammoxidation as well as preparation method and application of catalyst

    CN116060031A

  • Composite oxide catalyst, preparation method thereof and method for preparing nitrile compound

    CN116078394A

  • Fluid-bed catalyst for propylene ammoxidation to prepare acrylonitrile

    CN1810360A

Cited By

  • Acrylonitrile catalyst as well as preparation method and application thereof

    CN122183636A

  • A process for the preparation of a catalyst for the ammoxidation of propylene to acrylonitrile

    CN122183636B